Regulation of Blood Flow in the Cerebral Posterior Circulation by Parasympathetic Nerve Fibers: Physiological Background and Possible Clinical Implications in Patients With Vertebrobasilar Stroke - Tamayo, Arturo; Siepmann, Timo (Frontiers in Neurology, 2021)
The posterior circulation is represented by the vertebrobasilar arteries, which supply oxygen and glucose to vital human brainstem structures among others. This complex circulatory- perfusion system is not homogenous throughout the day; rather, its hemodynamic changes rely on physiological demands, ensuring brainstem perfusion. This dynamic autoregulatory pattern maintains cerebral perfusion during blood pressure changes. Accumulative evidence suggests that activity within the autonomic nervous system is involved in the regulation of cerebral blood flow. Both, the sympathetic and parasympathetic nervous systems do not work independently. Functional studies have shown a tight and complicated cross talk between these systems. In pathological processes where sympathetic stimulation is present, systemic vasoconstriction is followed, representing the most important CNS parasympathetic trigger that will promote local vasodilation. Stroke is a clear example of this process. The posterior circulation is affected in 30% of strokes, carrying high morbidity and mortality outcomes. Currently, the management of ischemic stroke is focused on thrombolytic treatment and endovascular thrombectomy within an overall tight 4.5 to 6 hours ischemic time window. Therefore, the autonomic nervous system could represent a potential therapeutic target to modulate reperfusion after cerebral ischemia through vasodilation, which could potentially decrease infarct size and increase the thrombolytic therapeutic ischemic window. In addition, shifting the autonomic nervous system balance toward its parasympathetic branch has shown to enhance neurogenesis and decrease local inflammation. Regretfully, the vast majority of animal models and human research on neuromodulation during brain ischemia have been focused on anterior circulation with disappointing results. In addition, the source of parasympathetic inputs in the vertebrobasilar system in humans is poorly understood, substantiating a gap and controversy in this area. Here, we reviewed current available literature regarding the parasympathetic vascular function and challenges of its stimulation in the vertebrobasilar system.